Upaya Peningkatan Motorik Kasar Anak Melalui Permainan Maze Sketch Spider untuk Anak Usia 5-6 Tahun di TK Bunga Bangsa 2 Grogol Jaya Depok - Mustika Dewi Muttaqien; Aisyah Aisyah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2021)
Abstract Based on the results of previous research at Bunga Bangsa 2 Kindergarten, it shows the low aspect of gross motor development for children aged 5-6 years is due to the gross motor development tools for children in Bunga Bangsa 2 Kindergarten are still not optimally used, and the lack of innovation in children's gross motor development games The purpose of this study was to improve the gross motor skills of children in group B1 of TK Bunga Bangsa 2 Gerogol Jaya Depok, by using a new game called maze sketch spider. The research method used is classroom action research. The sample was taken as many as 15 students. Data collection was carried out by direct observation and interviews with class teachers. The results showed: 1) Precycled observations, learning had not used the maze game and reached an average class percentage value of 47%. 2) Observation cycle I, learning has used the maze game and achieved an average class percentage value of 58%. 3) Observation cycle II, achieving an average class percentage value of 77%. So based on the results of research in cycle II, the results obtained have reached the specified success criteria of 75%. Therefore it can be concluded that with the maze sketch spider game, the gross motoric development of children in Group B1 of TK Bunga Bangsa 2 Gerogol Jaya Depok can increase with a class percentage of 77%.